Reconciling selves after sexual offending: exploring processes of desistance and impact on family members - Cohen, Miriam H. (The University of Edinburgh, 2021)
Aims: This thesis aimed to better understand the lived experiences of family members of individuals charged with cyber-enabled sexual offences (CESO). This explored the impact of the crime and its consequences on their subjective wellbeing. In addition, it investigated how family members made sense of this experience and how this translated to attempts to reconcile their view of themselves and repair their relationships with the other. This analysis was informed by an understanding of ‘desistance’ processes by which individuals move away from sexual offending. Methods: A systematic mixed-studies review was conducted on the topic of desistance from sexual offending. This included n = 16 qualitative studies and n = 10 quantitative studies. The evidence was analysed using a ‘best-fit’ framework synthesis, drawing from the ‘Integrated Theory of Desistance from Sexual Offending (ITDSO)’. A qualitative study was also conducted, interviewing n = 13 family members of individuals charged with CESO. This included romantic partners, parents and adult siblings. The narratives were analysed using a Multiperspectival Interpretative Phenomenological Analysis. Results: The review provided support for the ITDSO, whilst proposing amendments to further capture the complexity and unique considerations for those charged with sexual offences. These adaptations included hypothesised pathways of desistance and an understanding of the means by which desistance is promoted. The importance of social connection, forgiveness and belonging was emphasised, as well as barriers to re-entry and re-integration. Family member narratives provided main themes of ‘loss’, ‘cast out’, ‘silenced’ and ‘reconciliation’. Related themes of stigma, shame and trauma were pervasive throughout these. Conclusions: Societal perceptions and stigma of sexual offending shames individuals, preventing acquisition of goods that help to promote desistance or aid reintegration. This is true both for those convicted of crimes and individuals associated with them. Understanding reasons for the behaviour facilitates shifts towards prosocial identities and encourages forgiveness and reconciliation from those in their wider systems.
Keywords: desistance; sexual offending; systematic mixed studies review; sexual offending; indecent images of children; family members; Interpretative phenomenological analysis